ORGANIZASIONAL CULTURE AS MAIN DETERMINAN OF ELEMENTARY SCHOOL SUPERVISOR PERFORMANCE IN BENGKULU PROVINCE - Sumarsih Sumarsih Sumarsih (Manajer Pendididikan, 2016)
The objective of this research is to describe the affect of the organizasional culture on the elementary school supervisor in Bengkulu Province. The research was conducted by usingsurvey. The population are the elementary school supervisors. The sampel was collected proportional randomly from 100 elementary supervisors. Data were analized by using path analysis technique after all variabels put into correlation matrix. The result of research show there are positive direct effect of organizational culture on elementary school supervisors in Bengkulu Province.Keywords: organizational culture, supervisors dan performance